2018
DOI: 10.1002/2211-5463.12455
|View full text |Cite
|
Sign up to set email alerts
|

Elastin molecular aging promotes MDAMB‐231 breast cancer cell invasiveness

Abstract: Elastin is a long‐lived extracellular matrix protein responsible for the structural integrity and function of tissues. Breast cancer elastosis is a complex phenomenon resulting in both the deposition of elastotic masses and the local production of elastin fragments. In invasive human breast cancers, an increase in elastosis is correlated with severity of the disease and age of the patient. Elastin‐derived peptides ( EDP s) are a hallmark of aging and are matrikines – matrix fragments hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
(72 reference statements)
0
26
0
1
Order By: Relevance
“…ELN is a key component of the ECM family and plays critical roles in elasticity properties in soft tissues and may contribute to tumor formation. Previous studies have shown that ELN promotes human breast cancer cell invasiveness [7], indicating a potential role of ELN in cancer cell migration. However, the level of ELN in CRC has not been measured and the role of this molecule in CRC is not fully understood.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…ELN is a key component of the ECM family and plays critical roles in elasticity properties in soft tissues and may contribute to tumor formation. Previous studies have shown that ELN promotes human breast cancer cell invasiveness [7], indicating a potential role of ELN in cancer cell migration. However, the level of ELN in CRC has not been measured and the role of this molecule in CRC is not fully understood.…”
Section: Discussionmentioning
confidence: 93%
“…Human recombinant ELN (10 μg/ml, E6902, Sigma-Aldrich, St. Louis, USA) dissolved in sterile PBS was used to coat cell culture plates overnight at room temperature (RT). Control plates were coated with PBS only [7]. Human colon cancer epithelial cells (Caco-2, HTB-37, ATCC, Manassas, VA, USA) were seeded into each well of 24-or 96-well plate and cultured in Eagle's Minimum Essential Medium (EMEM) containing 2.5 mM L-glutamine, 10 mM HEPES and 10% FBS at 37°C with 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Neu-1 is a member of the sialidase family composed also of Neu-2, Neu-3, and Neu-4 (40). These exoglycosidases, widely distributed amongst species (41), remove terminal sialic acid residues from glycoproteins, glycolipids, and oligosaccharides.…”
Section: Neu-1 Tm Domain As a Potential Target In Cancersmentioning
confidence: 99%